Consumer Attitudes Towards Social Network Advertising: Predictors and Outcomes - Ivana Kursan Milaković; Mirela Mihić; Ivana Boljat (Tržište, 2020)
Purpose – This study explores the impact of perceived trust, search for novelty and perceived usefulness on consumer attitudes towards social network advertising, and the impact of those attitudes on buying intention, buying and word-of-mouth information spread. Design/Methodology/Approach – The research included convenience sample of 265 respondents. Online survey distributed through Facebook and Instagram was used as a research method. The data was analysed using a multiple regression analysis. Findings and implications – The results show that positive attitudes towards social network advertising depend on perceived trust and usefulness. The impact of the search for novelty on consumer attitudes towards social network advertising proved to be insignificant. Furthermore, buying intention, buying and disseminating information by word-of-mouth represent relevant outcomes of consumer attitudes towards social network advertising. This research has implications for companies in terms of a better understanding of the relevant predictors and outcomes of consumer attitudes in on-line advertising context. Managers can also benefit from the findings when creating successful communication strategies. Limitations – A major research limitation is the use of non-probability convenience sample that did not capture the population as a whole. Therefore, this may be regarded as a future research direction. Originality – This study sheds new light on relevant predictors and outcomes of consumer attitudes towards social network advertising, which was not previously researched from the proposed framework perspective.